CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

If $$y = \tan^{-1} \left [\dfrac {\sqrt {1 + x^{3}} + \sqrt {1 - x^{3}}}{\sqrt {1 + x^{3}} - \sqrt {1 - x^{3}}}\right ]$$, then $$y'$$ at $$x = 0$$ is


A
0
loader
B
32
loader
C
12
loader
D
32
loader

Solution

The correct option is A $$0$$
$$\cfrac { \sqrt { 1+{ x }^{ 3 } } +\sqrt { 1-{ x }^{ 3 } }  }{ \sqrt { 1+{ x }^{ 3 } } -\sqrt { 1-{ x }^{ 3 } }  } \\ =\left( \cfrac { \sqrt { 1+{ x }^{ 3 } } +\sqrt { 1-{ x }^{ 3 } }  }{ \sqrt { 1+{ x }^{ 3 } } -\sqrt { 1-{ x }^{ 3 } }  }  \right) \left( \cfrac { \sqrt { 1+{ x }^{ 3 } } +\sqrt { 1-{ x }^{ 3 } }  }{ \sqrt { 1+{ x }^{ 3 } } +\sqrt { 1-{ x }^{ 3 } }  }  \right) \\ =\cfrac { { \left( \sqrt { 1+{ x }^{ 3 } } +\sqrt { 1-{ x }^{ 3 } }  \right)  }^{ 2 } }{ { \left( \sqrt { 1+{ x }^{ 3 } }  \right)  }^{ 2 }-{ \left( \sqrt { 1-{ x }^{ 3 } }  \right)  }^{ 2 } } \\ =\cfrac { 1+{ x }^{ 3 }+1-{ x }^{ 3 }+2\sqrt { \left( 1+{ x }^{ 3 } \right) \left( 1-{ x }^{ 3 } \right)  }  }{ \left( 1+{ x }^{ 3 } \right) -\left( 1-{ x }^{ 3 } \right)  } \\ =\cfrac { 2-2{ x }^{ 3 }+2\sqrt { 1-{ x }^{ 6 } }  }{ 2{ x }^{ 3 } } \\ =\cfrac { 1-{ x }^{ 3 }+\sqrt { 1-{ x }^{ 6 } }  }{ { x }^{ 3 } } \\ \Rightarrow y=\tan ^{ -1 }{ \left[ \cfrac { 1-{ x }^{ 3 }+\sqrt { 1-{ x }^{ 6 } }  }{ { x }^{ 3 } }  \right]  } \\ \cfrac { dy }{ dx } =\cfrac { 1 }{ 1+\cfrac { { \left( 1-{ x }^{ 3 }+\sqrt { 1-{ x }^{ 6 } }  \right)  }^{ 2 } }{ { x }^{ 6 } }  } \times \cfrac { -3{ x }^{ 2 }\left( 1+\cfrac { 1 }{ \sqrt { 1+{ x }^{ 6 } }  }  \right)  }{ { x }^{ 6 } } \\ \Rightarrow { \left| \cfrac { dy }{ dx }  \right|  }_{ at\; x=0 }=0$$

Mathematics

Suggest Corrections
thumbs-up
 
0


similar_icon
Similar questions
View More



footer-image